A Host-Restricted Self-Attenuated Influenza Virus Provides Broad Pan-Influenza A Protection in a Mouse Model - Kim, Minjin; Cheong, Yucheol; Lee, Jinhee; Lim, Jongkwan; Byun, Sanguine; Jang, Yo Han; Seong, Baik Lin (Frontiers in Immunology, 2021)
Influenza virus infections can cause a broad range of symptoms, form mild respiratory problems to severe and fatal complications. While influenza virus poses a global health threat, the frequent antigenic change often significantly compromises the protective efficacy of seasonal vaccines, further increasing the vulnerability to viral infection. Therefore, it is in great need to employ strategies for the development of universal influenza vaccines (UIVs) which can elicit broad protection against diverse influenza viruses. Using a mouse infection model, we examined the breadth of protection of the caspase-triggered live attenuated influenza vaccine (ctLAIV), which was self-attenuated by the host caspase-dependent cleavage of internal viral proteins. A single vaccination in mice induced a broad reactive antibody response against four different influenza viruses, H1 and rH5 (HA group 1) and H3 and rH7 subtypes (HA group 2). Notably, despite the lack of detectable neutralizing antibodies, the vaccination provided heterosubtypic protection against the lethal challenge with the viruses. Sterile protection was confirmed by the complete absence of viral titers in the lungs and nasal turbinates after the challenge. Antibody-dependent cellular cytotoxicity (ADCC) activities of non-neutralizing antibodies contributed to cross-protection. The cross-protection remained robust even after in vivo depletion of T cells or NK cells, reflecting the strength and breadth of the antibody-dependent effector function. The robust mucosal secretion of sIgA reflects an additional level of cross-protection. Our data show that the host-restricted designer vaccine serves an option for developing a UIV, providing pan-influenza A protection against both group 1 and 2 influenza viruses. The present results of potency and breadth of protection from wild type and reassortant viruses addressed in the mouse model by single immunization merits further confirmation and validation, preferably in clinically relevant ferret models with wild type challenges.